EFFECTS OF TWO HEALTH EDUCATION INTERVENTIONS ON ADHERENCE TO ANTIHYPERTENSIVE MEDICATION AND ON BLOOD PRESSURE IN SELECTED TERTIARY HEALTH FACILITIES IN SOUTHWESTERN NIGERIA (2014)
Hypertension is often the precursor to cardiovascular disease complications with end-organ damage in poorly managed condition. Adherence to medication and appointment-keeping are critical in the control of hypertension and reduction of associated complications. However, poor adherence to treatment is common among hypertensive patients in clinical settings. Evidence-based health education interventions that can optimise patients’ adherence to medication and appointment-keeping are few in Nigeria. The study was therefore designed to explore the effects of two health education interventions on adherence to antihypertensive medication, appointment-keeping and Systolic Blood Pressure (SBP) implicated in end-organ pathology in selected tertiary health facilities in Southwestern Nigeria. The study was quasi-experimental involving patients receiving care in hypertensive clinics in three tertiary health institutions. The institutions were randomly allocated to Intervention 1 (Olabisi Onabanjo University Teaching Hospital, Sagamu), Intervention 2 (Lagos University Teaching Hospital, Lagos) and Control (University College Hospital, Ibadan) groups. Patient Education and Counselling (Intervention 1) and Patient Education and Counselling with Family-Support (Intervention 2) were implemented for four weeks. Baseline and follow-up evaluations employed a validated structured questionnaire to measure primary outcomes of Self-Reported Medication-Adherence (SRMA) on a 15-point scale, Appointment-Keeping (AK) on a 9-point scale and Pill Count (PC) from 60 participants purposively selected from each group. Secondary outcomes of SBP values were measured at baseline and followed up for nine weeks to determine changes in SBP. Data were analysed using descriptive statistics and ANOVA at p=0.05. Respondents were males (71.7%; 58.3%; 61.7%) and females (28.3%; 41.7%; 38.3%); and their ages were 52.1±6.5, 51.3±7.2 and 50.8±6.2 years for Intervention 1, Intervention 2 and Control groups respectively. The participants had non-formal (16.7%; 20.0%; 25%), primary (33.3%; 25.0%; 20.0%), secondary (26.7%; 16.7%; 20.0%) and post-secondary (15.0%; 23.3%; 18.3%) education for Intervention 1, Intervention 2 and Control groups respectively. At baseline, there were no significant differences in outcome measures among the three groups in respect of primary outcomes of SRMA (9.2±1.1; 9.1±1.0; 9.3±1.0), PC (57.9±5.1; 54.3±8.6; 58.9±4.6), AK (5.2±1.7; 5.1±1.0; 5.1±0.9) and secondary outcomes of SBP (159.0±8.7; 157.8±9.5; 155.4±8.4 mmHg) values respectively. At 13th week follow-up, Intervention 2 demonstrated significantly higher scores in respect of SRMA (14.4±0.7), PC (94.0±0.5), AK (8.9±0.3) with SBP reduction from 157.8±9.5 to 134.2±3.4 mmHg compared with Intervention 1 with SRMA (12.5±1.0), PC (89.5±0.6), AK (8.50±0.5) and a corresponding SBP reduction from 159.0±8.7 to 150.0±5.2 mmHg. The values of SRMA, PC and AK in control were 9.6±1.0, 59.6±0.6 and 5.8±1.0 respectively with SBP reduction from 155.4±8.4 to 154.0±6.9 mmHg. Furthermore, the magnitude of changes (∆) between outcome measures at 13th week follow-up and their respective baseline values for the three groups were ∆SRMA=3.3, ∆AK=3.3, ∆SBP=9.0 mmHg, ∆SRMA=5.3, ∆AK=3.8, ∆SBP=23.63 mmHg and ∆SRMA=1.2, ∆AK=5.4, ∆SBP=1.4 mmHg for Intervention 1, Intervention 2 and Control groups respectively. Intervention 2 results were significantly higher. The Patient Education and Counselling with Family-Support intervention was more effective in influencing adherence to appointment-keeping and medication–consumption leading to reduction in blood pressure. Therefore, it is recommended that family-support be incorporated in patient education strategies for effective control of hypertension.